Self-Guided Instructional Material: Fixed Partial Denture - Ranier Adarve; Lisa James (Association of American Medical Colleges, 2011)
Abstract This resource is a self-guided instructional module on fixed partial denture. It is designed primarily for dental students in preclinical programs as they learn and develop their skills in tooth preparation for fixed partial denture. It contains the outline of the step-by-step procedures, as well as photos that easily guide learners as they practice the skill. It also provides learners with information regarding the clinical implications of the procedure, thereby adding context and relevance. The use of this module is most beneficial for students who are new to the procedure and want to learn at their own pace. It is also designed for faculty members to augment their teaching resources for students. Both students and faculty can print the module and use it as a guide in learning fixed partial denture preparation. This module has been used in two dental schools in their preclinical fixed prosthodontic programs. Students reported positive feedback as regards its usefulness and ease of use. Faculty reported improved performance of students learning the skill.